Delectatio et decor ordinis. O teologii Jacka Salija - Jerzy Szymik (Warszawskie Studia Teologiczne, 2019)
Which word can summarise the huge oeuvre of father Jacek Salij? What is the key? How can you define the theology which is both Theocentric, and Christocentric; consequently ministerial towards the Church, man, “spiritual seekers”; constructive in theses and polemical; intransigent towards foolishness, naivety, barbarity; creative and deeply set in the most outstanding philosophical and theological tradition; creating identity and cooperating with culture, literature and arts; engaging all intellectual powers into matters of faith and ethos; professional, research, erudite and ministerial, close to life, existential; Polish and universal, substantively systematized and formally diverse...? Here is Thomas-like decor ordinis in Salij’s life and …